Metformin A Prospective Alternative for the Treatment of Chronic Diseases - Badria, Farid A. (IntechOpen, 2023)
Currently, there are many complicated health disorders with different etiologies and pathogeneses, including cancers, obesity, periodontitis, cardiovascular disease, liver, skin and renal disorders. It is now known that the causes and pathogenesis of many complex chronic diseases are usually polyfactorial: genetic, environmental, constitutive factors, or a combination of these. Recently, poly-target molecules containing enzymes capable of catalyzing several reactions have been efficiently used in the treatment of several metabolic disorders, and infectious and inflammatory diseases. This book describes the history of the discovery of metformin and its chemistry. Topics presented include new approaches to the role of metformin in the treatment of diabetic patients and its ability to target multiple signaling pathways.